GEOLOGICAL AND GEOMORPHOLOGICAL CHARACTERIZATION OF JOÃO PESSOA MUNICIPALITY – PB, BRAZIL - Silva-Barbosa, Tamires; Torres-Gomez, Laura Marcela; Furrier, Max (Revista Geográfica de América Central., 2016)
This paper aims at characterizing geological and geomorphological aspects of the township of João Pessoa, Paraíba State, through the creation of a geomorphological map with methodology developed in Brazil, based on morphostructural and morphostructural aspects. The geomorphological mapping of the town offers a wide range of information on lithological, morphometric, morphographic and morphogenetic data. This information is essential to any social space study, especially in relation to the occupation in different morphological attributes that would compose the municipality. The main results were the distinction and quantification of geological and geomorphological units present in the municipality and current geomorphological processes responsible for the genesis of contemporary forms of relief.